Acetylcholinesterase electrochemical biosensors with graphene-transition metal carbides nanocomposites modified for detection of organophosphate pesticides - Wang, Bo (PLoS One, 2020)
An acetylcholinesterase biosensor modified with graphene and transition metal carbides was prepared to detect organophosphorus pesticides. Cyclic voltammetry, differential pulse voltammetry, and electrochemical impedance spectroscopy were used to characterize the electrochemical catalysis of the biosensor: acetylcholinesterase/chitosan-transition metal carbides/graphene/glassy carbon electrode. With the joint modification of graphene and transition metal carbides, the biosensor has a good performance in detecting dichlorvos with a linear relationship from 11.31 μM to 22.6 nM and the limit of detection was 14.45 nM. Under the premise of parameter optimization, the biosensor showed a good catalytic performance for acetylcholine. Compared to the biosensors without modification, it expressed a better catalytic performance due to the excellent electrical properties, biocompatibility and high specific surface area of graphene, transition metal carbides. Finally, the biosensor exhibits good stability, which can be stored at room temperature for one month without significant performance degradation, and has practical potential for sample testing.